2021
DOI: 10.1088/1742-6596/2083/4/042063
|View full text |Cite
|
Sign up to set email alerts
|

Research on Intelligent Information System of Library under Big Data and Digitization Technology

Abstract: In the big data environment, we develop personalized information of college libraries based on big data from three aspects: the overall architecture of the system model, the functional model of the system, and the design of system interface modules according to the design principles and requirements of the personalized information service system of the university library Service system design. In terms of the functional design of the platform, the service platform is divided into four levels: accurate identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The service platform is based on accurate identification of user needs, personalization of artificial intelligence service settings, academic research based on integrated materials (Wang & Sha, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The service platform is based on accurate identification of user needs, personalization of artificial intelligence service settings, academic research based on integrated materials (Wang & Sha, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Chingath (2020) and Tella (2012) noted that students expect AR technology to enhance their overall library experience by providing more interactive and immersive services. Wang and Sha (2021) found that students who used an AR-based indoor positioning system in a library setting reported improved spatial orientation and satisfaction levels. These findings suggest that students have high expectations of AR in improving their library experience.…”
Section: Literature Reviewmentioning
confidence: 97%
“…On the contrary, AR has shown potential for enhancing learning experiences in libraries (Kannegiser, 2021). Previous studies (Su and Chen, 2022; Wang and Sha, 2021) have explored the use of advanced technologies, such as AR, to support information literacy instruction. In their findings, students who participated in AR-enhanced activities displayed improved engagement and retention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Big data is not something new that comes from nowhere. In 1980, the famous American thinker and futurist master Alventovler first proposed the concept of "data" and "big data" in The Third Wave (Wang & Sha, 2021). The book boldly shows that not only is data seen as wealth, but that big data will also be the highlight of the third wave of the revolution.…”
Section: Big Datamentioning
confidence: 99%